Local cOinage and Hospital Equipment Index (Lo Hei): projectile distance of Singapore coinage and healthcare-related equipment in a 3T magnetic resonance imaging scanner - Shao Jin Ong; James TPD Hallinan; Deborah Khoo; Desmond Hoon; Koon Liang Chia; Joanne Hang; Lycia Teo; Peijing Su; Michael Ong; Bertrand Ang; Swee Tian Quek (Singapore Medical Journal)
Introduction: Modern magnetic resonance imaging (MRI) scanners utilise superconducting magnets that are permanently active. Patients and healthcare professionals have been known to unintentionally introduce ferromagnetic objects into the scanning room. In this study, we evaluated the projectile risk of Singapore coinage as well as some common healthcare equipment within a 3 T MRI scanner. Methods: A rig termed ‘Object eNtry Guidance and Linear Acceleration Instrument’ (ONG LAI) was custom-built to facilitate safe trajectory of the putative ferromagnetic objects. A ballistic gel target was utilised as a human tissue surrogate to estimate tissue penetration. The point at which objects would self-propel towards the scanner was named ‘Huge Unintended Acceleration Towards Actual Harm (HUAT AH)’. Results: Singapore third-series coins (10-cent to 1-dollar coins) are highly ferromagnetic and would accelerate towards the MRI scanner from more than one metre away. Cannulas with their needles are ferromagnetic and would self-propel towards the scanner from a distance of 20 cm. Standard surgical masks are ferromagnetic and may lose their sealing efficacy when they are worn too close to the magnet. Among the tested objects, a can of pineapple drink (Lee Pineapple Juice) had the highest HUAT AH at a distance of more than 1.5 m. Conclusion: Some local coinage and commonly found objects within a healthcare setting demonstrate ferromagnetic activity with projectile potential from a distance of more than 1 m. Patients and healthcare professionals should be cognisant of the risk associated with introducing these objects into the MRI scanning room.